2015
DOI: 10.1507/endocrj.ej14-0529
|View full text |Cite
|
Sign up to set email alerts
|

Women with rigorously managed overt diabetes during pregnancy do not experience adverse infant outcomes but do remain at serious risk of postpartum diabetes

Abstract: The normal increase in insulin resistance from the third trimester of pregnancy can be greater than can be managed by compensatory insulin secretion, resulting in gestational diabetes mellitus (GDM) [1]. The severity of GDM is variable in pregnant women and it cannot be fully explained by known risk factors which include advanced maternal age, high maternal body mass index (BMI), weight gain during pregnancy, family history of diabetes, high fat diet, and certain ethnicities [1][2][3]. There are notable racial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Conversely, a UK study reported that screening based on random plasma glucose testing before 20 weeks had a sensitivity of 86% for detecting women with overt diabetes 27 showing superior sensitivity compared to HbA1c. Similar to our study, previous studies have also reported higher occurrences of adverse outcomes in women with overt diabetes than in those with GDM diagnosed in late pregnancy 28–30 . It was also shown that only one‐fifth of the women with overt diabetes maintained an HbA1c ≥50 mmol/mol postdelivery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, a UK study reported that screening based on random plasma glucose testing before 20 weeks had a sensitivity of 86% for detecting women with overt diabetes 27 showing superior sensitivity compared to HbA1c. Similar to our study, previous studies have also reported higher occurrences of adverse outcomes in women with overt diabetes than in those with GDM diagnosed in late pregnancy 28–30 . It was also shown that only one‐fifth of the women with overt diabetes maintained an HbA1c ≥50 mmol/mol postdelivery.…”
Section: Discussionsupporting
confidence: 90%
“…It was also shown that only one‐fifth of the women with overt diabetes maintained an HbA1c ≥50 mmol/mol postdelivery. A low rate of postpartum diabetes (21%) among women with overt diabetes had been reported previously by Wong et al, 28 but Park et al 30 reported a high rate of 73% despite good glycaemic control during pregnancy. Unlike our study, both studies used an OGTT for postpartum diabetes screening.…”
Section: Discussionmentioning
confidence: 58%
“…The literature on maternal diabetes and low Apgar score is not clear cut, but tends towards worse outcomes; [32, 33] although in one recent study that found worse Apgar scores associated with maternal diabetes, the association disappeared in an adjusted analysis [34] Whether the outcome was worse also appears to be associated with the level of glycaemic control [35]. Again, and in contrast with the results on birth outcome, the odds of recovery given a low 1 min Apgar score were better in uncomplicated vaginal deliveries born to mothers with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this suggests that when DIP is suspected, screening with FPG is insufficient and must be substituted by OGTT and/or HbA1c measurement. Two studies elsewhere showed that type 2 diabetes is confirmed by postpartum OGTT in 21.1% [27] to 47.5% [28] of women diagnosed with diabetes in pregnancy, with additional prediabetes identified in 32.5% to [28] 37.6% of cases [27]. Therefore, one can hypothesize that eDIP would correspond with pre-diabetic states prior to pregnancy, and that late-diagnosed DIP (with an initial normal FPG level) would correspond to some other mechanism, which would require further investigation.…”
Section: Is Diabetes In Pregnancy Different Between Early and Late Pregnancy?mentioning
confidence: 97%